Hakikat Dan Sistem Nilai Dalam Konteks Pendidikan - Khumaini Rosadi; Khojir (EDUSIANA Jurnal Manajemen dan Pendidikan Islam, 2023)
Human potential must be developed by studying and continuing to read as instructed by Allah in the first revelation, namely IQRA. In fact, this is the essence of education. Reading will be a good culture, whereas never reading will be a bad culture. Not just reading books in copies, but reading the book of life. Books that live within oneself and books that live in the environment, such as family, neighbors, society and social media. Therefore, every human being must communicate with others. Can't live alone. Because humans are social creatures, so get along with everyone well. Live your life by following the rules that apply in society. Don't just want to live as you please. Because humans have feelings, ethics and norms. This is the true essence of education. Gain value by respecting norms. Whether religious norms, social norms, or community norms. Because human values, whether good or bad, can be reflected in the way they behave in society, and this attitude is the result of education that they have learned in life and put into practice in their daily lives. Whether your grades are good or bad, it all depends on you. Because the potential value is in his attitude. Keywords: Essence of education, Good culture, Attitude.